2019
DOI: 10.1155/2019/2561530
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Detection in Head and Neck Squamous Cell Carcinomas at a Tertiary Hospital in Sub-Saharan Africa

Abstract: Fewer studies have been done over the years to establish the association of human papillomavirus (HPV) with head and neck squamous cell carcinoma (HNSSC) within the subregions of sub-Saharan Africa, and thus this study was designed to investigate the presence of HPV in HNSCC at a tertiary hospital in Ghana, providing additional evidence on the need to explore similar studies in other subregions. A retrospective cross-sectional study was employed to investigate the presence of the DNA of HPV genotypes in HNSCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The study population varied from 12 in a study from Ghana [ 12 ] to 42,024 in the USA [ 13 ], Table 1 . Most of the minor studies were observed in Middle Eastern and African countries ( n = 12–34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population varied from 12 in a study from Ghana [ 12 ] to 42,024 in the USA [ 13 ], Table 1 . Most of the minor studies were observed in Middle Eastern and African countries ( n = 12–34).…”
Section: Resultsmentioning
confidence: 99%
“…HPV detection methods varied among the included studies. Fifteen studies were based on double positivity with both HPV DNA PCR and p16 IHC ( n = 6624) [ 4 , 16 , 19 , 20 , 22 , 23 , 28 , 30 , 32 , 33 , 34 , 35 , 38 , 39 , 40 ], eight studies were based on HPV DNA alone ( n = 426) [ 12 , 14 , 15 , 24 , 25 , 29 , 36 , 41 ], six on p16 alone ( n = 391) [ 17 , 18 , 21 , 26 , 27 , 31 ], one study was based on both HPV DNA and HPV RNA ( n = 99) [ 37 ] and one study did not report a detection method ( n = 42,024) [ 13 ]. Most studies using p16 IHC defined p16-positivity (p16+) according to ASCO guidelines with ≥70% positive staining [ 42 ] ( n = 2663), but one study defined p16+ as ≥10% positive staining ( n = 30) [ 30 ], four studies defined p16+ as ≥75% positive staining ( n = 2678) [ 4 , 22 , 31 , 32 ] and one study did not account for p16-positivity ( n = 926) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, no country is spared since the responsibility for one of these new risk factors, infection by the ubiquitous human papillomavirus, is now well established. [25][26][27][28] As far as gender is concerned, the predominance is traditionally male with an overall sex ratio of 2.1 ranging from 5.2 for Central and Eastern Europe to 1.4 for North Africa, Western Asia and Oceania. 8 In Nairobi, Kenya, where the rate of oral cancer is one of the highest in sub-Saharan Africa, Parkin et al reported that the cumulative incidence of oral cancer is higher among women than among men.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors in the head and neck are including cancers in various anatomical sites including tumors of the oral cavity, nasopharynx, paranasal sinuses, and larynx [7]. Globally, tumors in the head and neck are recognized as one of the top five tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…About 95% of head and neck cancer begins in squamous cells and known as head and neck squamous cell carcinoma (HNSCC). Alcohol and tobacco are the major risk factors for causing and developing this type of tumor; recently, the Epstein-Barr virus (EBV) and the human papillomavirus (HPV) are also considered other risk factors for the nasopharyngeal and oropharyngeal cancers respectively [7,10]. Computed tomography (CT), routine magnetic resonance imaging, and laryngoscopy are the most commonly used diagnostic techniques for that type of cancer [11].…”
Section: Introductionmentioning
confidence: 99%